Evaluation of the effectiveness of the technology of biological treatment of wastewater at the Salar aeration station. (Texas Journal of Agriculture and Biological Sciences, 2023)
The article , 2 strains of chlorella algae and 5 species of aquatic plants were grown in domesticcommunal wastewater, and the resistant species were selected from among them. , development and productivity, as well as information on the physical and chemical properties of wastewater before and after the growth of algae and aquatic plants. The obtained results showed that Pistia and Eichhornia algae and aquatic plants developed rapidly in 100% wastewater, with high productivity and improved physicochemical properties